Caregiver Burden and Spiritual Well-being in Caregivers of Hemodialysis Patients - Rafati, Foozieh (Journal of religion and health, 2020)
The number of hemodialysis patients is increasing worldwide, and the caregivers of these patients experience a great burden. This study was conducted to examine the relationship between caregiver burden and spiritual well-being in caregivers of hemodialysis patients in Kerman, Iran. This correlational study was conducted on 382 caregivers of hemodialysis patients. Data were collected using the Caregiver Burden Inventory (24 items) and Ellison and Paloutzian 20-Item Spiritual Well-being Questionnaire. Data were analyzed by descriptive and inferential statistics (t test, ANOVA, Spearman correlation, and linear regression analysis) in SPSS 20 software. The findings showed that 45 (11.8%) caregivers had mild, 214 (56%) moderate, and 123 (32.2%) high caregiver burden. Furthermore, 1 (0.3%) caregiver had mild, 349 (92.4%) moderate, and 32 (8.4%) high spiritual well-being. Also, Spearman correlation test showed a significant reveres relationship between caregiver burden and spiritual well-being scores (p < 0.001, r = − 0.41). Moreover, the results of the regression analysis showed that the patient’s income, frequency of patient dialysis per week, and patient’s need to receive care and spiritual well-being were predictors of caregiver burden, which explained 41% of the burden in caregivers. The results of this study revealed that spiritual well-being was negatively related to caregiver burden and was one of its predictors. Therefore, spirituality can be used as a low-cost and effective intervention to reduce the caregiver’s burden.